2022
DOI: 10.1109/access.2022.3146414
|View full text |Cite
|
Sign up to set email alerts
|

Switchable Multi-Wavelength Thulium-Doped Fiber Laser Using a Cascaded or Two-Segment Sagnac Loop Filter

Abstract: A switchable multi-wavelength thulium-doped fiber laser (TDFL) using either two-stage cascaded or two-segment Sagnac loop filters are proposed and analyzed. Both filters incorporate a 3-m and 1.7-m long polarization-maintaining fiber, which acts as a comb filter. By adjusting two polarization controllers, when the TDFL used a cascaded Sagnac loop filter, eight stable single-wavelength operations were obtained with easy switching among them. The wavelength range was 16.36 nm during the singlewavelength switchab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 27 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Until 2022, Sulaiman et al researched the effect of a hybrid optical amplifier on a multi-wavelength fiber laser utilizing the Sagnac loop mirror interferometer [18]. Embedding a PC in the loop has a certain tuning effect [19], but the connection between the PC and the optical coupler (OC) brings greater insertion loss.…”
Section: Introductionmentioning
confidence: 99%
“…Until 2022, Sulaiman et al researched the effect of a hybrid optical amplifier on a multi-wavelength fiber laser utilizing the Sagnac loop mirror interferometer [18]. Embedding a PC in the loop has a certain tuning effect [19], but the connection between the PC and the optical coupler (OC) brings greater insertion loss.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al reported a six-wavelength-switchable TDFL based on a polarizationmaintaining sampled FBG, in which the wavelength fluctuation was as low as 0.71 dB [14]. Li et al reported a stable and tunable TDFL based on two Sagnac loop filters, where the wavelength tuning range was 16.36 nm, OSNR was up to 55 dB for dual-wavelength laser output, and maximum and minimum wavelength spacings were 21.78 nm and 1.50 nm, respectively [15].…”
Section: Introductionmentioning
confidence: 99%